ChemInform Abstract: A Novel Nonanuclear Hafnium Oxide—Hydroxide—Sulfate Cluster Crystallized from Aqueous Solution. Issue 13 (1st April 2014) - Kalaji, A.; Soderholm, L.
Abstract Single crystals of (NH4)14 [Hf9O8(OH)6(SO4)14] ·nH2O (n ≅ 12.5) are grown by heating an aqueous solution of HfOCl2, (NH4)2SO4, and H2SO4 (pH 0.93, sealed glass vial, 80 °C, 10 d; 54% yield).